Molecular characterization of a novel capillovirus from red currant - Petrzik, Karel; Přibylová, Jaroslava; Koloniuk, Igor; Špak, Josef (Archives of virology, 2016)
The complete nucleotide sequence of a novel virus from red currant, provisionally named currant virus A (CuVA), was determined. The genome is 7925 nucleotides long and has a 3'-poly(A) tail. The genome organization with two overlapping open reading frames is similar to that of capilloviruses, but the CuVA genome is about 600 nucleotides longer than that of the longest known capillovirus, cherry virus A. The RNA is predicted to encode a polyprotein with domains of methyltransferase, 2OG-Fe(II) oxygenase, papain-like protease, RNA helicase, RdRp, and capsid protein. Phylogenetic analysis confirms that CuVA is a new and distinct member of the genus Capillovirus.
Keywords: genom virový; regulace exprese virových genů; RNA virová; Phylogeny; RNA, Viral; nemoci rostlin; Genome, Viral; fylogeneze; Flexiviridae; Gene Expression Regulation, Viral; Ribes; Plant Diseases; Viral Proteins; virové proteiny